Factors related to HIV disclosure in 2 South African communities - Norman, Amy; Chopra, Mickey; Kadiyala, Suneetha (American Public Health Association, 2007)
Disclosure of HIV status is an essential part of behavior modification and access and adherence to treatment in people infected with HIV.We conducted interviews in 2 South African communities of similar ethnic mix but with very different rates of disclosure of HIV status and found that disclosure was the catalyst for access to a variety of important and often essential resources. In the community with high rates of disclosure of HIV infection, disclosure led to greater access to formal institutional support and opportunities to take positive leadership roles in the community.Our findings highlight the prominence of wider sociopolitical contexts for disclosure decisionmaking and the need for HIV interventions to increase levels of disclosure of HIV infection.